2020
DOI: 10.1109/access.2020.2984785
|View full text |Cite
|
Sign up to set email alerts
|

Clock Synchronization in Wireless Sensor Networks Based on Bayesian Estimation

Abstract: Clock synchronization is essential for the operation of upper layer applications in Wireless Sensor Networks. When the network hops needed for clock synchronization message transmission is large, synchronization error will accumulate and synchronization accuracy may be reduced significantly. Moreover, in the existing synchronization algorithms, large number of communication resources and node energy will be expended in sending and receiving time messages. To solve the problem, this paper proposes a Bayesian es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In Section II-D it was shown that when analyzing the case of a WBAN with broadcast timing message dissemination, the message delay reduces to the expression (8). Given its random nature, to reduce the reception time t R at its minimum, the RMQM routine processes the synchronization packet with the highest priority with respect to every other possible ∆T M (j) = ∆T(j) S S (j) + 1 (37) that represents the equivalent accumulated time difference between the master and the slave in a single slot T M .…”
Section: Received Messages Queue Management (Rmqm) Routinementioning
confidence: 99%
“…In Section II-D it was shown that when analyzing the case of a WBAN with broadcast timing message dissemination, the message delay reduces to the expression (8). Given its random nature, to reduce the reception time t R at its minimum, the RMQM routine processes the synchronization packet with the highest priority with respect to every other possible ∆T M (j) = ∆T(j) S S (j) + 1 (37) that represents the equivalent accumulated time difference between the master and the slave in a single slot T M .…”
Section: Received Messages Queue Management (Rmqm) Routinementioning
confidence: 99%
“…We focus our attention on the state-of-theart solutions for such limitations because they affect any localization technique regardless of the measurement employed in the localization process, contrary to the particular limitations. Recent solutions for the particular limitations related to time, signal strength, and angular based localization techniques can be found in [99][100][101], [17,102], and [103][104][105], respectively.…”
Section: Recent Solutionsmentioning
confidence: 99%
“…Traditional schemes obtain timestamps in the MAC (Media Access Control), and multiple time delays occur in the process of transmitting the message to the antenna, such as sending delay, access delay, transmission delay, and receiving processing delay. The transmission delay, access delay, and receiving processing delay are uncertain delays, which usually bring microsecond or millisecond errors and greatly impact the clock synchronization accuracy [17]. Therefore, traditional clock synchronization schemes always have low accuracy due to inaccurate timestamp data, as shown in Figure 3.…”
Section: The General Architecture Of Hybsyncmentioning
confidence: 99%